2004
DOI: 10.1159/000079666
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Overload and Cardiac Function

Abstract: The changes in cardiac function caused by calcium overload are reviewed. Intracellular Ca2+ may increase in different structures [e.g. sarcoplasmic reticulum (SR), cytoplasm and mitochondria] to an excessive level which induces electrical and mechanical abnormalities in cardiac tissues. The electrical manifestations of Ca2+ overload include arrhythmias caused by oscillatory (Vos) and non-oscillatory (Vex) potentials. The mechanical manifestations include a decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 82 publications
(204 reference statements)
2
24
0
2
Order By: Relevance
“…The basis for this heightened proclivity of PCs to develop arrhythmic behavior is not fully known, although the diminished T-tubular density8, altered action potential morphology33, altered kinetics of Ca 2+ handling (Fig 2) and increased intracellular Na + load10 may all be contributory factors. In addition, the participation of IP 3 -sensitive Ca 2+ channels as part of the excitation-contraction coupling machinery may also influence this arrhythmogenic behavior9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for this heightened proclivity of PCs to develop arrhythmic behavior is not fully known, although the diminished T-tubular density8, altered action potential morphology33, altered kinetics of Ca 2+ handling (Fig 2) and increased intracellular Na + load10 may all be contributory factors. In addition, the participation of IP 3 -sensitive Ca 2+ channels as part of the excitation-contraction coupling machinery may also influence this arrhythmogenic behavior9.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying ultrastructural features such as a decreased T-tubular density8, the presence of IP 3 -sensitive Ca 2+ channels9, and susceptibility to Ca 2+ overload due to greater Na + load10 may in part account for the propensity of these specialized cells to develop abnormal Ca 2+ release events. Moreover, recent data suggest that higher diastolic Ca i -voltage coupling gain in Purkinje fibers may underlie the generation delayed after-depolarizations (DADs) and triggered beats11.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of digitalis glycosides on cardiac arrhythmias are well documented (Gheorghiade et al, 2004; Vassalle and Lin, 2004). In our laboratory, we used strophanthidin to induce cardiac arrhythmias in the ventricular tissues of large animal (such as dog) (Lin and Vassalle, 1978) and failing human myocardium (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we used strophanthidin to induce cardiac arrhythmias in the ventricular tissues of large animal (such as dog) (Lin and Vassalle, 1978) and failing human myocardium (Lee et al, 2004). Strophanthidin can induce calcium overload and triggered rhythms (Lin and Vassalle, 1978; Vassalle and Lin, 2004). While the combination of ISO and strophanthidin increased the incidence of AF in the mXinα+/+ LA-PV preparations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Among others, high levels of catecholamines have been discussed as one potential mechanism causing the development of TC. On the other hand, it was demonstrated that electrical disturbances may be caused by toxic catecholamine excess 1. However, the simultaneous occurrence of both TC and congenital electrical disease has to this date been reported in only two cases 2, 3.…”
Section: Discussionmentioning
confidence: 99%